A factor analysis of an instrument for measuring physical abuse experience of students at school - Safrudin Amin; Badrun Kartowagiran; Pracha Inang (REID (Research and Evaluation in Education), 2018)
Violence in schools is increasingly reported by the mass media. It indicates that its prevalence is escalating. An instrument which has a proper psychometric property is needed to investigate the phenomenon. The study aims to develop an instrument for measuring physical abuse experienced by students in schools and explore the construct of the instrument. To pursue those objectives, the content validitity, construct validity, and reliability analysis on the developed instrument were measured. Its content validity was confirmed through expert judgment, construct validity was proven through exploratory factor analysis, and reliability was estimated through Cronbach’s alpha coefficient. Experts considered that the content of all items were relevant, though they also suggested some improvement in wordings for greater clarity. The exploratory factor analysis on 31 items indicates that seven items need to be dropped and 24 items are divided into three factors called (1) victimized by friends with the loading factor ranging from 0.44 to 0.69, (2) victimizing friends with the loading factor ranging from 0.45 to 0.66, and (3) being victimized by teachers with the loading factor ranging from 0.57 to 0.68. The reliability of the test was 0.874. Based on this result, the developed instruments consist of three factors with good validity and reliability.